Lean Practices, Warehouse Performance & Customer Satisfaction - A Study on Electrical & Electronics Manufacturing in China - Hui, Edmund Koh Chung; QINGHAI, WANG; Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
Literatures have recognized lean production and lean warehouse as a prominent manufacturing philosophy that is based on customer-focused process improvements. To further enhance customer satisfaction performance, many electrical & electronics manufacturers are turning to lean manufacturing practices to increase their business performance. However, numerous studies argued that the theory and practice show inconsistent results between lean practices and warehouse performance. In China context, , few researches have been conducted on lean warehouse practices in electrical & electronics manufacturing. Therefore, this study seeks to establish the inter-relationship of lean warehouse practices of standardization, supplier network, quality at source and inventory management and customer satisfaction, in China electrical & electronics manufacturing and underpinned by the Resource-Based View (RBV). A quantitative and a cross-sectional research design were adopted, and one hundred and fifty two research questionnaires were administered to managers/executives in China. A valid response of 129 questionnaires was obtained and the data was analyzed using the SPSS and Smart PLS. From the research outcome, the hypothesized relationship between lean practices of standardization and warehouse’s customer satisfaction was supported. Secondly, the hypothesized relationship between lean practices of supplier network and warehouse customer satisfaction was supported. Thirdly, the hypothesized relationship between lean practices of quality at source and warehouse’s customer satisfaction was also supported. Finally, the hypothesized between lean practices of inventory management and warehouse’s customer satisfaction was not supported. Research limitations, future research and conclusion were discussed in this study.